Increased α‐tocopherol metabolism in horses with equine neuroaxonal dystrophy. (31st July 2021) - Hales, Erin N.; Habib, Hadi; Favro, Gianna; Katzman, Scott; Sakai, R. Russell; Marquardt, Sabin; Bordbari, Matthew H.; Ming‐Whitfield, Brittni; Peterson, Janel; Dahlgren, Anna R.; Rivas, Victor; Ramirez, Carolina Alanis; et al.
Abstract: Background: Equine neuroaxonal dystrophy/equine degenerative myeloencephalopathy (eNAD/EDM) is an inherited neurodegenerative disorder associated with a vitamin E deficiency within the first year of life. Vitamin E consists of 8 isoforms metabolized by the CYP4F2 enzyme. No antemortem diagnostic test currently exists for eNAD/EDM. Hypothesis/Objectives: Based on the association of α‐tocopherol deficiency with the development of eNAD/EDM, we hypothesized that the rate of α‐tocopherol, but not γ‐tocopherol or tocotrienol metabolism, would be increased in eNAD/EDM‐affected horses. Animals: Vitamin E metabolism: Proof of concept (POC) study; eNAD/EDM‐affected (n = 5) and control (n = 6) horses. Validation study: eNAD/EDM‐affected Quarter Horses (QHs; n = 6), cervical vertebral compressive myelopathy affected (n = 6) horses and control (n = 29) horses. CYP4F2 expression and copy number: eNAD/EDM‐affected (n = 12) and age‐ and sex‐matched control (n = 11‐12) horses. Methods: The rates of α‐tocopherol/tocotrienol and γ‐tocopherol/tocotrienol metabolism were assessed in equine serum (POC and validation) and urine (POC only) using liquid chromatography tandem mass spectrometry (LC‐MS/MS). Quantitative reverse‐transcriptase PCR (qRT‐PCR) and droplet digital (dd)‐PCR were used to assay expression and genomic copy number of a CYP4F2 equine ortholog. Results: Metabolic rate of α‐tocopherol was increased in eNAD/EDM horses (POC, P < .0001; validation, P = .03), with no difference in the metabolic rate of γ‐tocopherol. Horses with eNAD/EDM had increased expression of the CYP4F2 equine orthologue ( P = .02) but no differences in copy number. Conclusions and Clinical Importance: Increased α‐tocopherol metabolism in eNAD/EDM‐affected QHs provides novel insight into alterations in vitamin E processing in eNAD/EDM and highlights the need for high‐dose supplementation to prevent the clinical phenotype in genetically susceptible horses.